Serum selenium levels in patients with respiratory diseases: a prospective observational study - Lee, Yo-Han; Lee, Seok Jeong; Lee, Myoung Kyu; Lee, Won-Yeon; Yong, Suk Joong; Kim, Sang-Ha (Journal of Thoracic Disease, 2016)
Background: Serum selenium levels are lower in critically ill patients as compared with healthy controls. However, there is no data about the difference in serum selenium levels depending on the severity of lung diseases. We aimed to identify the factors associated with low serum selenium levels in critically ill patients with respiratory diseases. Methods: A prospective study was performed in 83 patients with respiratory diseases who had admitted to the intensive care unit (ICU) and general wards. We obtained systemic inflammatory markers, nutritional indicators and prognostic factors as the explanatory variables for the outcome of low serum selenium levels. Results: Serum selenium levels on admission were lower by 28% in the ICU group as compared with the general ward group (70.0±26.4 and 97.9±20.8 ng/mL, respectively, P